2022
DOI: 10.3390/cells11193008
|View full text |Cite
|
Sign up to set email alerts
|

m6A Modification of Long Non-Coding RNA HNF1A-AS1 Facilitates Cell Cycle Progression in Colorectal Cancer via IGF2BP2-Mediated CCND1 mRNA Stabilization

Abstract: Background: Long non-coding RNAs modulate tumor occurrence through different molecular mechanisms. It had been reported that HNF1A-AS1 (HNF1A Antisense RNA 1) was differently expressed in multiple tumors. The role of HNF1A-AS1 in colorectal cancer was less analyzed, and the mechanism of regulating the cell cycle has not been completely elucidated. Methods: Differentially expressed lncRNAs were screened out from the TCGA database. HNF1A-AS1 was examined in CRC clinical samples and cell lines by RT-qPCR. CCK8 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Our results revealed DNA methylation as an apparent modifier of angiogenesis by altering transcription and upregulating expression of different angiogenesis regulators. That includes the transcription factors Sox17 , a promotor of endothelial sprouting behavior and differentiation as well VEGFR2 expression in a cell-intrinsic manner, and ETS transcription factors family member Erg , that transactivate genes involved in key endothelial functions like survival, VEGF-angiogenic signaling pathways along with the VEGF receptor Flt1 , [ 59 64 ]. Furthermore, altered DNA methylation regulates extracellular matrix remodeling, forming a more proangiogenic matrix by upregulating fibronectin ( Fn1 ) and thrombospondin-4 ( Thbs4 ) expression, and increasing expression of integrin β5, which is responsible for the cell–matrix interaction [ 65 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed DNA methylation as an apparent modifier of angiogenesis by altering transcription and upregulating expression of different angiogenesis regulators. That includes the transcription factors Sox17 , a promotor of endothelial sprouting behavior and differentiation as well VEGFR2 expression in a cell-intrinsic manner, and ETS transcription factors family member Erg , that transactivate genes involved in key endothelial functions like survival, VEGF-angiogenic signaling pathways along with the VEGF receptor Flt1 , [ 59 64 ]. Furthermore, altered DNA methylation regulates extracellular matrix remodeling, forming a more proangiogenic matrix by upregulating fibronectin ( Fn1 ) and thrombospondin-4 ( Thbs4 ) expression, and increasing expression of integrin β5, which is responsible for the cell–matrix interaction [ 65 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that METTL3 installed the m6A modification and enhanced lncRNA HNF1A-AS1 transcript stability to increase HNF1A-AS1 expression. Upregulated HNF1A-AS1 increased the level of CCND1 by suppressing PDCD4, sponging miR-93-5p and enhancing IGF2BP2-mediated CCND1 mRNA stabilization, which accelerated CRC cell-cycle progression and reduced cell apoptosis (41). Research has found that METTL3 promotes the cell proliferation and glycolysis of CRC by upregulating oncogenic lncRNA PTTG3P.…”
Section: Effects Of Mettl3 On Crcmentioning
confidence: 99%
“…6 Some lncRNAs, including MALAT1, TUG, NEAT1 and HNF1A-AS1, are reported to be dysregulated in CRC, playing a role in regulating the development and progression of intestinal cancer. [7][8][9][10] N6-methyladenosine (m6A) is the most prevalent modification found in eukaryotic RNA. 11 The process of RNA m6A methylation is dynamic and reversible, and involves three types of proteins: methyltransferases, recognition proteins and demethyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Our recent research has shown that HNF1A-AS1 promotes IGF2BP3 recognition of the m6A modification region of CCND1, thereby stabilizing CCND1 and promoting colon cancer cell growth and metastasis. 7 However, the specific functions and molecular mechanisms of most other lncRNAs and IGF2BP1 in CRC are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation